Finanse gminy samorządowej de lege lata i de lege ferenda - Małecki, Jerzy (Wydział Prawa i Administracji UAM, 1991)
Bringing back to life the territorial self-government in Poland makes it necessary to define the legal grounds of its financial activity. To accomplish this task, it is necessary to amend the Constitution and many statutes of lower rank. Financial legislation presently in force is highly inadequate. On the one hand, there are still many regulations adopted during the communist period, and, on the other hand, new financial legislation is of provisional or blank rule character. Besides, financial regulations pertaining to communes are diffused in many legislative acts. Hence, it is necessary to prepare and pass a new statute (code) on financial economy of communes.
Finances of a self-governing commune de lege lata and de lege ferenda